Characterization of Terpenoids in the Essential Oil Extracted from the Aerial Parts of Scrophularia Subaphylla Growing in Iran - Parina Asgharian; Fariba Heshmati Afshar; Solmaz Asnaashari; Sedigheh Bamdad Moghaddam; Atefeh Ebrahimi; Abbas Delazar (Tabriz University of Medical Sciences, 2015)
Purpose: The aim of this work was to investigate the volatiles released from aerial parts of Scrophularia subaphylla (Scrophulariaceae) which is a perennial herb growing in Azarbaijan province in Iran. Methods: A combination of GC-MS and GC-FID were applied for analyzing the chemical compositions of the essential oil extracted by hydro-distillation from the aerial parts of Scrophularia subaphylla (S. subaphylla). Results: Thirty six compounds, representing 97.32% of total oil were identified. High content of terpenoids (60.02%) were identified in the essential oil with Linalool (22.35%), phytol (15.74%) and geraniol (7.27%) as the most dominant compounds, while other main components were representatives of fatty acids (24.31%), indicated mainly by palmitinic acid (17.29%). DPPH assay was used for assessing the antioxidant properties of compounds. However, no remarkable free radical scavenging activity was observed. Furthermore, Disc diffusion method was applied for evaluating the antimicrobial activity of essential oil vs. gram positive and gram negative bacteria strains. The examined oil showed weak antibacterial effect. Conclusion: Main constituents of S. subaphylla were terpenoids. In comparison with other genesis of Scrophularia, antioxidant and anti bacterial properties of S. subaphylla essential oil were not noticeable.